ASSESSMENT OF TOLERANCE AND STABILITY IN BARLEY (HORDEUM VULGARE L.) GENOTYPES AT EARLY SEEDLING GROWTH STAGE UNDER SALINE CONDITION - Askari, Hossein; Kazemitabar, Seiyed Kamal; Zarrini, Hamid Najafi; Saberi, Mohammd Hossein (Plant Breeding and Seed Science, 2018)
This study was performed to assess several indices for identifying genotypes at early growth stage with the best performance in salinity conditions. In order to evaluate the biomass production of barley genotypes in different levels of salt conditions, an experiment was conducted as factorial arrangement with a completely randomized design with 3 replications. The effect of salinity treatments was studied through an analysis of the dry matter production, yielding results that show significant differences among genotypes. The majority of used tolerance indices indicated that ESBYTM8910, 4 Shori and MBS8715 were the best barley genotypes showing the highest stress resistance for the greatest NaCl concentration. Based on used stability parameters the genotypes MBS8712 and Jo torsh were the most phenotypically stable. Result of cluster analysis revealed that tolerant genotypes showed the least stability based on mostly of stability parameters. In general, results showed the WB7910, ESBYTM8910 and MBS8715 genotypes appeared better than others across the salinity levels.